Dizziness After Traumatic Brain Injury: A Prospective TRACK-TBI Analysis of Risk Factors, Quality of Life, and Neurocognitive Effects. Issue 10 (6th December 2022) - Chae, Ricky; Barber, Jason; Temkin, Nancy R.; Sharon, Jeffrey D.
Abstract : Objective: To determine the longitudinal incidence of dizziness and its association with demographic factors, neurocognitive effects, functionality, and quality of life. Study Design: Transforming Research and Clinical Knowledge in Traumatic Brain Injury (TRACK-TBI) is a prospective, longitudinal cohort study in which TBI patients were assessed at the emergency department and 2-week, 3-month, 6-month, and 12-month follow-up via telephone and/or in-person visits. Setting: Multicenter study in emergency departments of 18 academic medical centers in the United States. Patients: A total of 1, 514 patients 17 years or older with a diagnosis of TBI, injury occurrence within 24 hours of admission, fluency in English or Spanish, and completed Rivermead Post-Concussion Symptoms Questionnaire (RPQ) at 12 months were enrolled between February 2014 and August 2018. Main Outcome Measure: RPQ, Short Form-12 Version 2, Wechsler Adult Intelligence Scale IV, Trail Making Test, Patient Health Questionnaire-9, PROMIS-PAIN, and Glasgow Outcome Scale–Extended Revised. The primary outcome measure was a self-report of "feelings of dizziness" on RPQ at 12 months post-TBI. Results: Of the 1, 514 participants, 1, 002 (66%) were male and 512 (34%) were female. The mean age was 41.6 (SD, 17.4) years. At 12 months, 26% experienced dizziness, with 9% experiencing moderate or severe dizziness. Dizziness was strongly associated with headache (odds ratio [OR], 3.45; 95% confidence interval [CI], 2.92–4.07; p < 0.001), nausea (OR, 4.43; 95% CI, 3.45–5.69; p < 0.001), worse hearing (OR, 3.57; 95% CI, 2.64–4.82; p < 0.001), noise sensitivity (OR, 3.02; 95% CI, 2.54–3.59; p < 0.001), and light sensitivity (OR, 3.51; 95% CI, 2.91–4.23; p < 0.001). In multivariable regression models, participants with severe dizziness demonstrated lower performance compared with those without new or worse dizziness on the Wechsler Adult Intelligence Scale IV (−6.64; p < 0.001), Trail Making Test part A (7.90; p = 0.003) and part B (19.77; p = 0.028), and Short Form-12 physical (−13.60; p < 0.001) and mental health (−11.17; p < 0.001), after controlling for age, sex, education, and TBI severity. Conclusion: Dizziness is common among TBI patients and relates to quality of life and neurocognitive performance.